Money Wages, Prices, and Causality - Mehra, Y. P. (Journal of Political Economy, 1977)
Using recently developed statistical techniques for examining the causal patterns between two variables within a bivariate distributed lag system, it is shown that, for the U.S. historical sample period 1954-70, money wages and consumer prices are simultaneously determined. This bidirectional feedback structure between wages and prices appears very strongly at the manufacturing level, though there is some evidence that such a structure does hold at the industry level, too. The structure of the casual patterns observed between industry money wages and prices for this sample period is not related to the industry market structure.